If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6/x-4=3/x-5
We move all terms to the left:
6/x-4-(3/x-5)=0
Domain of the equation: x!=0
x∈R
Domain of the equation: x-5)!=0We get rid of parentheses
x∈R
6/x-3/x+5-4=0
We multiply all the terms by the denominator
5*x-4*x+6-3=0
We add all the numbers together, and all the variables
x+3=0
We move all terms containing x to the left, all other terms to the right
x=-3
| x-4/3x-5=-2 | | 10=2y=18 | | 1/2=4d | | x=3/2=x-6 | | -3(x+2)=2(x-8) | | -2+3x=-8=12x | | 5^-3y=4 | | 4^-2(5-2x)=-2 | | 5(x-4)+2(x+6)=5x+8 | | 4(b-3)+4(b+2)=3b+31 | | 2^-3=4x-1 | | M/2.2+4=13x2.2 | | 7x+35+1=9(x-9)+23 | | 3(-2x+6)=-54 | | 12c=0.6c= | | 3b-9+4b+8=3(b+9) | | 3b-9+4b+8=3(b+9 | | 4m-8=2(m-1) | | q=7000-100(1000) | | x/2+2x+2=100 | | 9^3x+1=25 | | 3(a+2)+2(a-4)=3a+10 | | 0=-16x^2+255 | | 5(x2+x-12)(x-8)=0 | | 3(7-4)=x | | 25y=17y+75 | | 54/m=9 | | 13/9x-6=15/74 | | X/y=-9.6 | | -0.4=g/3-9.0 | | 6c+3=c+43 | | -7u+41=6(u+9) |